“Sapiando” : produto educacional para o ensino sobre anfibiofauna na modalidade da educação de jovens e adultos - Pinheiro, Débora Dutra (2014)
The young and adult education established across time, as a mean to provide to people that did not had opportunity to start or progress their studies, to return to school to improve and actualize their right to education. Historically, the students of this educational method are workers and often sought literacy. Is required to provide both literacy and a good high school, with specific methodologies and educational practices. In this work it was proposed an educational product grounding in the andragogy principles and in the significantly learning theory . The educational product “Sapiando” was produced to give to the teacher of Biology a theoretical and didactic framework to the instruction about the amphibian fauna, content of the high school curriculum. Furthermore, a historical review and the state of art of Biology teaching research was evaluated. With the qualitative analysis of the results of “Sapiando” application in the classroom, it is possible to infer that the educational product effectively contribute to the significantly learning.